Dating Violence: A Report from Legal and Victimological Perspective - Baindowi, Salimi Muhammad (Faculty of Law Universitas Negeri Semarang, 2021)
Violence against women is a manifestation of the historical inequality of power relations between men and women. This results in the emergence of domination and discrimination against women by men, so that this condition will become an obstacle to their progress. Violence against women, in this case related to dating violence, is one of the social mechanisms that needs attention, because it encourages women in a subordinate position compared to men. The purpose of this study is to find out how the concept and form of the criminal act of Dating Violence is. In addition, this study also aims to find out how the victimization of dating violence is reviewed and legal protection for victims of dating violence.